Situation Report: Hungary, 9 January 1969 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Coverage of Smrkovsky Affair Hilton Hotel to Be Built in Budapest Suicide of Gyorgy Peter Shell Gasoline Stations to Be Built TU Organization Vetoes Management Decision on Production Norms Changes of Prices in 1969 in the Spirit of the NEM